2012
DOI: 10.1007/s13197-012-0649-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoghurt or yoghurt serum on microbial quality of cig kofte

Abstract: Cig kofte, raw meatball is a traditionally produced meat product in Turkey and some other Middle East countries. It is prepared from mixtures of finely minced raw beef, bulgur, onions, various spices and tap water. Cig kofte is an uncooked product and popularly consumed with lettuce and lemon juice. In this study, yoghurt or yoghurt serum (YS) were added to the mixtures of cig kofte instead of tap water to reduce microbial risks of the raw meatball. Additionally, the effects of yoghurt and YS on some physicoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 13 publications
3
9
2
Order By: Relevance
“…The color properties of cig kofte samples were investigated by Dogan et al . () and they reported L* , a* and b* values of the samples to be similar to the results in the present study and in the range of 40–42, 15.6–16.3 and 27.4–29, respectively.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The color properties of cig kofte samples were investigated by Dogan et al . () and they reported L* , a* and b* values of the samples to be similar to the results in the present study and in the range of 40–42, 15.6–16.3 and 27.4–29, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Dogan et al . () reported that the DM content of cig kofte samples prepared using meat was in the range of 46.25–49.72%, and they stated that the DM content of cig kofte is affected directly from the ingredients used in the production. pH and a w are two important intrinsic factors determining the growth of microorganisms in foods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study indicated replacing water with yoghurt and yoghurt serum in the formulation. Researchers stated its potential for preventing foodborne pathogens in Cig Kofte [8].…”
Section: Resultsmentioning
confidence: 99%